2016
DOI: 10.1037/a0039669
|View full text |Cite
|
Sign up to set email alerts
|

Use of family-friendly work arrangements and work–family conflict: Crossover effects in dual-earner couples.

Abstract: This study uses a dyadic approach to examine how an employee's work-family conflict is affected when his or her partner makes use of family-friendly work arrangements. We focused on 2 types of family-friendly practices, that is, reduced work hours and schedule or workplace flexibility. Hypotheses were tested with multilevel structural equation modeling using information of 186 dual-earner couples. In line with our hypotheses, we found support for both a positive and a negative crossover effect, though the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…These elements of the gloomy perspective can reduce work performance, hinder recovery, detract from WLB, and create work-family conflict. In fact, among the 37 studies reviewed here, study samples include those from Finland (Kinnunen et al, 2017), Belgium (Schooreel & Verbruggen, 2016), El Salvador (Las Heras, Rofcanin, Bal, & Stollberger, 2017, and the Netherlands (Biron & Van Veldhoven, 2016;Derks et al, 2015;LaPierre, Steenbergen, Peeters, & Kluwer, 2016;ten Brummelhuis & Van der Lippe, 2010). This suggests that this is not only the fastest growing stream of research but also perhaps the most diverse and generalizable mechanism of work-family backlash in terms of cross-cultural implications.…”
Section: Mechanism 3: Spillovermentioning
confidence: 90%
“…These elements of the gloomy perspective can reduce work performance, hinder recovery, detract from WLB, and create work-family conflict. In fact, among the 37 studies reviewed here, study samples include those from Finland (Kinnunen et al, 2017), Belgium (Schooreel & Verbruggen, 2016), El Salvador (Las Heras, Rofcanin, Bal, & Stollberger, 2017, and the Netherlands (Biron & Van Veldhoven, 2016;Derks et al, 2015;LaPierre, Steenbergen, Peeters, & Kluwer, 2016;ten Brummelhuis & Van der Lippe, 2010). This suggests that this is not only the fastest growing stream of research but also perhaps the most diverse and generalizable mechanism of work-family backlash in terms of cross-cultural implications.…”
Section: Mechanism 3: Spillovermentioning
confidence: 90%
“…In line with Greenhaus and Powell’s (2003) vignette manipulation for perceived home pressure, we narrowed down the private environment to one aspect, i.e., the partner, to make interpretation of the vignette easier for respondents (Aguinis and Bradley, 2014). We specifically choose for the partner as work-home decisions are often made at a couple level (Moen and Yu, 2000) and work-home practice use has shown to have cross-over effects on work-home conflict (Schooreel and Verbruggen, 2015). A manipulation check, which asked respondents to what extent the employee in the vignette experienced pressure from his/her partner (1: ‘No pressure at all’ – 7: ‘A lot of pressure’), showed that in line with our manipulation, respondents reported significantly more pressure in the ‘home pressure’ condition than in the ‘no home pressure’ condition ( F (1,547) = 402.12, p < 0.01, for vignettes on telework; F (1,546) = 505.12, p < 0.01, for vignettes on part-time work).…”
Section: Materials and Methods Of Studymentioning
confidence: 99%
“…For example, boundary theory explains how individuals have preferences for and enact different boundaries surrounding their work and family spaces (Ashforth, Kreiner, & Fugate, 2000; Nippert‐Eng, 1996; Rothbard, Phillips, & Dumas, 2005). Multiple studies have investigated how WFSs (e.g., flextime and flexplace) shape employees' preferences to segment or to integrate work and family boundaries for themselves as well as in coordination with their partners, and, ultimately, how these efforts affect their attitudes, behaviors, and well‐being (e.g., Bryan & Sevilla, 2017; Lautsch, Kossek, & Eaton, 2009; Radcliffe & Cassell, 2015; Schooreel & Verbruggen, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…FWA studies with work–family outcomes have provided insight into the value experienced within both family and work domains and across relationships between dual‐earner couples, supervisors to employees, and among coworkers. For example, in a multilevel study of Belgian dual‐earner couples, Schooreel and Verbruggen (2016) found positive cross‐over effects in which employees perceived more social support and experienced a decrease in both time‐ and strain‐based work family conflict when the employee's partner used flextime or flexplace arrangements. We do note, however, that the authors also found this effect weakens when the employee themselves utilized FWAs.…”
Section: Flexible Work Arrangements (Fwas)mentioning
confidence: 99%